Apolipoprotein E ε4 Allele-Based Differences in Brain Volumes Are Largely Uniform Across Late Middle Aged and Older Hispanic/Latino- and Non-Hispanic/Latino Whites Without Dementia - Stickel, Ariana M.; McKinnon, Andrew C.; Matijevic, Stephanie; Grilli, Matthew D.; Ruiz, John; Ryan, Lee (Frontiers in Aging Neuroscience, 2021)
Hispanics/Latinos are at equal or greater risk for Alzheimer’s disease (AD), yet risk factors remain more poorly characterized as compared to non-Hispanic/Latino Whites. Among non-Hispanic/Latino White cohorts, the apolipoprotein (APOE) ɛ4 allele is one of the strongest risk factors for AD with subtle declines in episodic memory and brain volumes detectable in preclinical stages. We examined whether APOE ɛ4 status had a differential impact on cognition and brain volumes among cognitively healthy and mild cognitively impaired Hispanics/Latinos (n = 86; ɛ4 n = 23) compared to a well-matched group of non-Hispanic/Latino Whites (n = 92; ɛ4 n = 29). Neither APOE ɛ4 status nor the interaction between ɛ4 status and ethnicity was associated with cognitive performance. APOE ɛ4 status was associated with white matter, but not gray matter, volumes. APOE ɛ4 carriers had significantly smaller whole brain white matter volumes as well as smaller right middle temporal and left superior temporal volumes. Hispanics/Latinos had significantly smaller left middle frontal gray matter volumes yet marginally larger overall white matter volumes than non-Hispanic/Latino Whites. Exploratory analysis within the Hispanic/Latino sample found that those whose primary language was Spanish had larger whole brain white matter volumes compared to primarily English speakers. Importantly, primary language differences only held for Hispanic/Latino ɛ4 carriers and did not differentiate Hispanic/Latino non-carriers, underscoring the need for further investigation into the impacts of language and acculturation on cognitive aging among the fastest growing ethnic minority group in the United States.